Epidemiological Study of CA Breast in Diyala - Rihab Ibrahim Ahmed; Shahab Ahmed Shakir; Mohamad Tyeyab Hamad; Nazar Saleh Ibrahim (Diyala Journal of Medicine, 2022)
Background: Breast cancer is becoming the most common cancer among women in both developed and developing countries . Breast cancer has been the leading cause of death among Iraqi women for three decades, and it is the second leading cause of death after cerebrovascular illnesses.